2006
DOI: 10.1111/j.1365-2664.2006.01209.x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of rain forest fragmentation on butterflies in northern Borneo: species richness, turnover and the value of small fragments

Abstract: Summary 1.Widespread and rapid losses of tropical rain forests have made understanding the responses of species to rain forest fragmentation an area of major concern. In this study we examined the impacts of habitat fragmentation on the species richness and faunal composition of butterflies in tropical rain forests in Sabah, Borneo. We analysed patterns of both α -and β -diversity to assess the relative importance of differences in patch size, isolation and vegetation structure on the diversity and similarity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 65 publications
9
96
1
2
Order By: Relevance
“…Small fragments often experience increased habitat disturbance (this study; [27]) and altered micro-climates, and whether or not changes in trophic organization Figure 6. Maximally ordered species presence-absence matrix for (a) fruit-feeding moths and (b) fruit-feeding butterflies in rainforest fragments in Sabah, Borneo.…”
Section: Discussion (A) Comparisons Of Sars Among Taxamentioning
confidence: 91%
See 1 more Smart Citation
“…Small fragments often experience increased habitat disturbance (this study; [27]) and altered micro-climates, and whether or not changes in trophic organization Figure 6. Maximally ordered species presence-absence matrix for (a) fruit-feeding moths and (b) fruit-feeding butterflies in rainforest fragments in Sabah, Borneo.…”
Section: Discussion (A) Comparisons Of Sars Among Taxamentioning
confidence: 91%
“…As an index of vagility, we measured butterfly forewing length in the field (+1 mm using vernier calipers), and obtained data on moth forewing length from published sources [66 -71]. To assess the vulnerability of species to local extinction, butterflies and moths were assigned to four geographical range size groups ( [27]; endemic to Borneo, restricted to Sundaland, restricted to the Oriental region, occurring beyond the Oriental region (using data from [66][67][68][69][70][71]85])).…”
Section: Methods (A) Avian Responses To Fragmentation (I) Source Datamentioning
confidence: 99%
“…Additionally, butterfly richness has been suggested as being positively correlated with habitat area, following the classic species-area relationship (Ricklefs & Lovette, 1999;Benedick et al, 2006). An empirical example is provided by Uehara-Prado et al (2007), where a positive relationship was found between fragment area and species richness of fruit-feeding butterflies in the Atlantic forest.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that SAG is a small Amazon forest remnant inserted in a matrix of villages and crops, it is possible that sensitive butterfly species have already become locally extinct due the reduced size and habitat heterogeneity of this forest patch, impacting the observed species richness. Interestingly, despite presenting low species richness, small forest fragments can still contribute substantially to regional diversity (Benedick et al, 2006), since these areas can maintain species that are no longer present in disturbed habitats nearby.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, conservation efforts have focused either on large and relatively undisturbed habitats because large areas conserve relatively more species (Laurance 2005), or on biodiversity hotspots with exceptional concentrations of endemic species under relatively high levels of threat (Myers et al 2000). However, conserving a number of small habitat patches such as sacred groves can have additional value for conserving biodiversity, for instance by covering a wider variety of habitats than would be achieved by protecting a few large patches of an equivalent total area (Bhagwat and Rutte 2006;Hokkanen et al 2009) and thus contributing to higher total biodiversity covered (Benedick et al 2006). Another important benefit is that a habitat network enabling dispersal amongst sacred groves and other protected areas (Laita et al 2010;Chiarucci et al 2012) may make an important contribution to genetic connectivity (Lander et al 2010) and the survival of species as metapopulations (sensu Hanski 1998).…”
Section: Introductionmentioning
confidence: 99%